Cultures and organizations : software of the mind: intercultural cooperation and its importance for survival - Hofstede, Geert , 1928-; Hofstede, Gert Jan; Minkov, Michael (McGraw-Hill, 2010)
A study of how the place where we grew up shapes the way we think, feel, and act - with new dimensions and perspectives. Based on research conducted in more than seventy countries over a forty-year span, this title examines what drives people apart - when cooperation is so clearly in everyone's interest.